PEMBERDAYAANPARAPENYANDANGTUNANETRA MELALUI REHABILITASI BERBASIS MASYARAKAT - Sari Rudiyati (LPMPP Universitas Negeri Yogyakarta, 2003)
'Educational and or rehabilitation services for people with visualempairment in Indonesia are estimated not to have reached visuallyimpaired peoplewho have attained the age of25 years old and livein rural areas that have never received educational and orrehabilitation services so that they are powerless in their life. It isthen necessary to develop empowering programs for visuallyimpaired people through community-based education and orrehabilitation.In general such programs aim at an even distributionof theequal chance to get education and or rehabilitation for those living inthe rural areas who are already outside schoolage but have never goteducation and or rehabilitation. The programs especially aim tocreate situations making it possible for everyone with visualimpairmentto live normally their whole life and have a selfconfidence and a feelingof being; close neighbors with other people;to help the family, neighbors, and other membersof the communityto accept, appreciate, and comfortably give assistance if necessary tothe people with visual impairment in their life; and to give an equalchance and appreciate the abilities and all the potentials that the° visually impaired people have.The advantagesof the empowering programs for people withvisual impairment are that the programs are simple,inexpensive,ollIld very realistic; they serve these people in their own society based-ontheir potentials and individual needs; and the family and othercommunity members are involvedin the implementation process ofthe education and or rehabilitation ofpeople with visual impairment